Strategi Konservasi Keanekaragaman Hayati dan Mitigasi Bencana Longsor melalui Program Agrosiaga di Desa Peron - Muhammad Agnaf Naufal; Aurelia Dias Nanda Revalina; Daffa Evan Pradama; Bernov Lakhomi Pujangga Sakti; Karista Gadis Setiyanda; Umi Rahmawati; Maria Nafraim Oktavian; Amnan Haris (BERDAYA Indonesian Journal of Community Empowerment, 2024)
Climate change and environmental degradation pose serious threats to ecosystem sustainability, particularly in forest-village areas that are vulnerable to ecological disasters. Peron Village is one such forest village with potential commodities such as coffee, aren, rubber, and avocado. However, it also faces the risks of landslides and negative interactions with wild animals. To address these challenges, the PPK Ormawa HIMA IPA dan Lingkungan UNNES, implemented the Agrosiaga Program, which was designed through a Training of Trainer (ToT) approach combined with conservation planting activities. The program included biodiversity education, wildlife handling training, and the planting of tabebuya and avocado seedlings as buffer plants on sloping areas. The results indicated an improvement in community knowledge and awareness of environmental conservation, along with a paradigm shift in perceiving wildlife that was previously considered a threat. Therefore, the Agrosiaga  can be regarded as a model of forest-village empowerment that integrates ecological, social, and economic aspects in a synergistic manner and has the potential to be replicated in other villages facing similar challenges.